Robust Tracking Control of Robot Manipulators Using Only Joint Position Measurements. (5th November 2013) - Zhang, Ancai; She, Jinhua; Lai, Xuzhi; Wu, Min; Qiu, Jianlong; Chen, Xiangyong
Abstract : This paper concerns the tracking control of a robot manipulator with unknown uncertainties and disturbances. It presents a new control method that uses only joint position measurements to design a tracking controller. The controller has two parts. One is based on a feedback linearization technique; it makes the nominal model of a manipulator asymptotically track a desired trajectory. The other is based on the idea of equivalent input disturbance (EID); it compensates for uncertainties and disturbances. Together they enable a robot manipulator to precisely track the desired trajectory. The new control algorithm is applied to a two-link robot manipulator, and simulation results demonstrate the validity of this method.